INOVASI PELAYANAN PUBLIK: PENERAPAN SISTEM INFORMASI MANAJEMEN PERIZINAN ONLINE DI KABUPATEN LEBAK - Nikki Prafitri (Majalah Ilmiah Dinamika Administrasi (MIDA), 2023)
Public service innovation is a form of public service effort to respond and be more adaptive to the needs of the community. Technology-based public service innovation is applied to create efficiency and effectiveness in public services. The Lebak Regency Government provides innovative online-based licensing services through SIMPONIE which is managed by the Investment Office and One-Stop Integrated Services of Lebak Regency. This study aims to determine the innovation of online-based public services through SIMPONIE in Lebak Regency. The research method used in this study is a causative research method. The results showed that public service innovation through SIMPONIE in Lebak Regency has been running well. This is characterized by the ease of service felt by users, adaptation to the use of SIMPONIE supported by good officer skills and responses, continuous socialization, simple procedures, evaluation from the community for improvement, increased retribution although still fluctuating and the way SIMPONIE works is transparent and can always be monitored. The effectiveness of public service innovation in the field of licensing can be created if there is effective socialization, readiness of service provider apparatus resources, adequate facilities and infrastructure and aspects of supervision through community participation as an evaluation function. Keywords; Public Service Innovation; Licensing; SYMPONIE